Participação do receptor CCR3 na migração de eosinófilos induzida por estrogênio para o útero de camundongos C57/BL6 ovariectomizados - Araújo, Jéssica Maria Dantas (2017)
Eosinophils are commonly described as cells from innate immunity that act on parasitic infections and lung diseases. However, in recent years, new functions are being added to these cells, among them, the maintenance of reproductive homeostasis. In addition, since the 1960s, studies have shown the estrogen relationship and the selective eosinophils migration to the uterus of castrated rats. The elucidation of the mechanism for the migration of these cells appears to be based on findings showing that the CCR3 receptor and its CCL11 chemokine are expressed in the human endometrium. Objective: The objective of this study was to evaluate the CCR3 participation in the eosinophils migration to the uterus of castrated mice, induced by 17-β-estradiol (E2). Methods: C57/BL6 mice, which received subcutaneous E2 injection, were used to determine the time and dose response of E2 (times 6, 12, 24 and 48 hours and doses of 0.1, 1, 3, 10, 30, 100 and 300 μg/kg) that promotes uterine weight gain and eosinophil migration. Subsequently, using the air bubble model, we sought to standardize CCL11- induced eosinophil recruitment, and the dose of the CCR3 antagonist (SB 328437 at doses of 1, 3 and 10 mg/kg) which promotes reduction in eosinophils migration. In addition, in the same model, the effect of the uterine extract with and without the administration of E2 (at the times of 6, 12 and 24 h) on the leukocyte migration was evaluated. Finally, an investigation was carried out on the effect of SB 328437 on uterine weight and eosinophil recruitment. The eosinophil peroxidase (EPO) absorbance and histology were used to evaluate the eosinophil migration, in which the uterus was stained with orcein specific for eosinophils. Results: The results demonstrated that the dose of 100 μg/kg E2 in the 24 hour period promoted a 40% increase in uterine weight, accompanied by eosinophil migration. In the air bubble model, it was observed that CCL11 recruited eosinophils, and SB 328437 promoted a 55% reduction in migration of these cells. The extract of the uterus caused the migration of total and eosinophilic leukocytes, but there was no difference between the groups with and without the administration of E2. Corroborating the results of SB 328437 in the air bubble experiment, the evaluation of its effect on uterine weight and eosinophils recruitment demonstrated that dose of 3 mg/kg reduced both parameters (approximately 45% and 56%, respectively) when stimulated with E2. The results were analyzed using ANOVA with Tukey post-test (more than two groups), and t test (two groups). Conclusion: Based on the results, it was possible to confirm the hypothesis that the CCR3 receptor participates in the eosinophils migration to the uterus of C57/BL6 mice after E2 induction. Furthermore, it represents an important pathway to be considered in studies aimed at elucidating mechanisms in in physiological and pathological processes involving the eosinophils recruitment.